Studies of cellular hypersensitivity to ionising radiation in Friedreich's ataxia. Issue 12 (December 1982) - Chamberlain, S; Lewis, P D
Abstract : Skin fibroblasts from seven patients with Friedreich's ataxia showed a small but significant increase in sensitivity to ionising radiation, as measured by post-irradiation clonal growth, when compared with cells from ten age-matched control subjects and from eight patients with motor neuron disease. Fibroblasts from three patients with Friedreich's ataxia also showed impairment of their ability to repair potentially lethal damage after ionising radiation. These findings are consistent with the view that defective DNA reparative mechanisms may be involved in the pathogenesis of Friedreich's ataxia.